Peningkatan Hasil Belajar Biologi Siswa Melalui Pengembangan LKPD Berbasis Directed Activities Related To Texts - Chandra Sagul Haratua; Usman Siswanto; Wahyu Budi Setiono; Fikri Sahrial; Husni Hamid (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to find out: Develop DARTs-based student worksheets to improve student Biology learning outcomes. The method used in this research is research and development which follows the steps of the Borg & Gall method and refers to previously established procedures. The LKPD developed was assessed by several experts in their respective fields, namely Biology experts, learning methods experts and language experts. The results of the research and development concluded: 1) The results of developing student worksheets (LKPD) based on DARTs were developed using several steps, and also tested the validity of three experts, namely Biology experts who gave a percentage of 89.58%, learning methods experts who gave a percentage of 87. .5% and language experts gave a percentage of 87.5%. This shows that the DARTs-based LKPD is valid and suitable for use for biology learning.